Building information modelling (Bim) for estimation of heat flux from streetscape material - Roslan R.; Omar R.C.; Roslan R.; Baharuddin I.N.Z.; Wahab W.A.; Hari Z.; Dzulkifli N.A.; Sanusi K.A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Streetscape elements are the major contributors to the urban heat island (UHI) phenomenon in the built urban environment. The hot surface air in this phenomenon is concentrated in urban regions and will gradually decrease in surrounding temperatures in suburban or rural regions. The effect of UHI can be seen through the increasing of land surface temperature and influencing the urban ecological systems, climates, and environments. A study has been conducted to identify the impact of urban heat island surrounding the PMUs streetscape furniture. In this study, the UHI variation has been investigated using BEM and city scale model. The UHI obtained were analyzed and modeled using satellite imagery and GIS. The 3D models of the PMUs faade were also been developed by using a laser scanner and thermal camera. Based on the analyses, the existing condition of seven selected PMUs are very high for Bangsar, High for Abu Bakar Baginda, Jalan Meru and Batu 4 Kuantan, Medium-high for Kuantan North and Taman Jaya and medium for Setia Alam. Land Surface Temperature (LST) in PMU facade is ranging between 23 C to55C. Building information modeling (BIM) analysis shows that the existing material used in most PMU facades with solar reflectance was uniformly low to medium-low. Building information modelling (BIM) result shows the building will give greater heat flux (+42% to +53% at 3 pm) because of the solar reflectance (%) from the facades of surrounding streetscape material used. By obtaining the information regarding the elements and factors that contribute to the UHI phenomenon within the study area, the reduction of heat absorption can be performed. BEIESP.